1990
DOI: 10.1080/07435809009033010
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of An Estrogen Receptor in the Submandibular and Parotid Salivary Glands of Female Rats

Abstract: The purpose of this study was to measure the availability of the estrogen receptor in submandibular and parotid salivary glands in female rats. The presence of a specific, competitive, and saturable estrogen binder in rat salivary gland tissue was determined by saturation analysis and steroid competition in cell-free homogenates of salivary gland tissue from adult ovariectomized females. Scatchard analysis of the data indicated an estrogen receptor content of 1971.1 +/- 651.4 femtomoles/gm of tissue in submand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…In contrast to our findings, the estrogenreceptor has been identified in rat SMG homogenates by others using binding studies (6) or immunohistochemistry in normal and castrated rats (27,31). Although from these studies it was clear that the estrogen-receptor was located in ductal cells, there is no consensus about the cell type that is the most important in this respect.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, the estrogenreceptor has been identified in rat SMG homogenates by others using binding studies (6) or immunohistochemistry in normal and castrated rats (27,31). Although from these studies it was clear that the estrogen-receptor was located in ductal cells, there is no consensus about the cell type that is the most important in this respect.…”
Section: Discussioncontrasting
confidence: 99%
“…Testosterone was found to increase and estrogen and/or progesterone to decrease the total granular duct area considerably (30). Further evidence for a regulatory role of steroids in rat SMG functioning comes from receptor binding assays and immunohistochemical studies demonstrating the presence of estrogen-and progesterone-receptors in the ductal system of the SMG (6,25,27,31). The presence of these hormone receptors suggests that the SMG could be a target in toxicity studies with estrogens, progestagens, and combinations of both.…”
Section: Introductionmentioning
confidence: 99%
“…If this indication is confirmed by quantitative analysis, then this finding would be consistent with the observations of other investigators. Thus, significant tissue-, gender-and species-differences have been identified in sex steroid receptor mRNA and protein expression, as well as in sex hormone binding activity, nuclear uptake and/or retention in nonocular sites (Abdelgadir et al 1990;Asaithambi et al 1997;Bergman et al 1987;Campbell et al 1990;Godwin & Crews 1999;Roselli & Resko 1997;Sheridan & Weaker 1982;Young et al 1995;Zhang et al 1989). Sex steroids may also up-or down-regulate the levels of their own or other sex steroid receptors (Blanchere et al 1998;Clark et al 1992;Saceda et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on receptors for other hormones known to influence the GCT cells, such as the receptors for thyroid hormones, adrenocorticosteroids, progesterone, or estrogens. Campbell et al (1990) and Sakabe et al (1987Sakabe et al ( , 1988 kinetically characterized the receptors for progestin and estrogen in extracts of the rat SMG; the latter authors have immunocytochemically localized them to cells of the GCT and striated ducts. Ozono et al (1991) confirmed the immunohistochemical localization of the progesterone receptor in GCT and striated duct cells and showed that expression of this receptor is increased by estradiol treatment.…”
Section: Hormone Receptorsmentioning
confidence: 99%